3D printed bone repair material as well as preparation method and application thereof

By adding infrared stimulation response materials, hydroxyapatite and bone active drugs to the PLA substrate, the prepared 3D printed bone repair material accelerates the bone repair speed under near-infrared light stimulation, solving the problems of both mechanical properties and bone repair effects of existing materials, and achieving efficient and flexible bone repair effects.

CN119656378APending Publication Date: 2025-03-21HANGZHOU JUFENG NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411881740.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing bone repair materials are difficult to have excellent mechanical properties and bone repair effects, and are poor in flexibility under external forces and are prone to damage.

Method used

3D printed bone repair materials are prepared using PLA as the substrate and combined with infrared stimulation-responsive materials (such as MXene), hydroxyapatite and bone-active drugs. Under the stimulation of external near-infrared light, infrared stimulation responds to the heat of the material, promotes the release of hydroxyapatite and bone-active drugs, improves the speed of bone repair, and enhances the mechanical strength and flexibility of the material.

Benefits of technology

The bone repair material has been able to significantly accelerate the bone repair speed under infrared stimulation, and has excellent mechanical properties and 3D printing moldability. The printed scaffold model is flexible, has high mechanical strength, and is biocompatible.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119656378A_ABST
    Figure CN119656378A_ABST
Patent Text Reader

Abstract

The invention discloses a 3D printed bone repair material as well as a preparation method and application thereof, and the 3D printed bone repair material is prepared from the following raw materials in parts by mass: 70-90 parts of polylactic acid, 0.1-5 parts of an infrared stimulation response material, 5-18 parts of hydroxyapatite, 0.1-5 parts of a bone active medicine, 0.1-0.5 part of an antioxidant and 0.1-0.5 part of a lubricant. The 3D printed bone repair material prepared by taking PLA as a base material and cooperating with the infrared excitation response material, hydroxyapatite, the bone active medicine and other raw materials can efficiently promote bone repair and also has excellent mechanical properties and 3D printing formability, and a printed stent model is good in flexibility and high in mechanical strength. Under the action of infrared light, the release of hydroxyapatite and bone active drugs in the PLA matrix can be accelerated, the bone repair speed is greatly improved, and the repair effect is good and fast.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of medical auxiliary materials, and in particular to a 3D printed bone repair material and a preparation method and application thereof. Background Art

[0002] Bone defects caused by trauma, infection, disease (osteoporosis and tumors) or surgical resection require bone grafting to fill. Autologous bone grafting is considered the gold standard among all clinically available graft materials because of its lowest risk of immune rejection, strong osteoinductivity and osteogenicity. However, the application of autologous bone grafting remains limited due to scarce supply and complications at the donor site. Allogeneic bone grafting is an alternative to autologous bone grafting, and the shape and size of allogeneic bone can be changed to adapt to bone defects. However, these commercialized allogeneic bones are expensive, have low osteoinductive activity, and have potential risks of disease transmission and immune rejection. Therefore, there is an urgent need to find an ideal bioactive material to repair bone defects.

[0003] Tissue engineering scaffolds represented by PLA are simple to prepare, low-cost, and have excellent degradability, mechanical strength and biocompatibility. In recent years, they have become a research hotspot in the field of bone tissue repair engineering technology. However, PLA scaffolds themselves lack osteoinductive activity and are difficult to promote the repair of bone defects when used alone, resulting in a low degree of integration between the scaffold and the bone. Therefore, it is necessary to modify and modify the PLA scaffold to improve the degree of repair of bone defects by the PLA scaffold.

[0004] Ti3C2T X It is a MXene material etched by MAX. Studies have shown that Ti3C2T X It has good biosafety and excellent osteoinductive activity, and can significantly promote the repair of bone defects. In addition, as a member of the MXene family, Ti3C2T X It has stable and efficient near-infrared (NIR) response characteristics. Under the irradiation of near-infrared light, it can further regulate the speed of bone defect repair through mild photothermal therapy and improve the efficacy of bone repair. It is expected to become an effective way to modify PLA scaffolds.

[0005] Publication No. CN115737931A discloses a 3D printed bone tissue repair scaffold material and a preparation method thereof, wherein the scaffold material body is a biphasic calcium phosphate carrying MXene (Ti3C2) and berberine and is cross-linked by sodium alginate, wherein the mass ratio of the biphasic calcium phosphate, sodium alginate, MXene (Ti3C2) and berberine is 60:6:0.025-0.125:0.05, and the biphasic calcium phosphate material is a mixture of hydroxyapatite and β-tricalcium phosphate, and the scaffold material body has a mutually interpenetrating macroscopic pore structure with a pore size of 300 μm. The 3D printed bone tissue repair scaffold material and the preparation method thereof disclosed in the invention have biphasic calcium phosphate, sodium alginate, MXene (Ti3C2) and berberine as the original materials, and have good biocompatibility and bone repairability. However, the main materials of the scaffold material are all inorganic substances, and the finished product has poor flexibility and is easily damaged under the action of external forces.

[0006] Similarly, publication number CN110935059A discloses a MXene composite bone repair material with photothermal function and its preparation method. The repair material includes the following components by weight: 0.3-3% MXene, 30-60% silk fibroin, 20-38.8% collagen, and 9.5-30% hydroxyapatite. However, its 3D printing can only adopt the low-temperature 3D printing method based on the discrete / stacking forming principle, and the flexibility and mechanical properties of the product are poor. Summary of the invention

[0007] In view of the fact that bone defect repair materials are difficult to have both mechanical properties and bone repair effects, the present invention provides a 3D printing bone repair material with PLA as the base material. The material has excellent mechanical properties and good 3D printing effect, and can promote the release of hydroxyapatite and active drugs under infrared stimulation, thereby significantly accelerating the speed of bone repair.

[0008] To achieve the above object, the technical solution adopted by the present invention is:

[0009] A 3D printed bone repair material, comprising the following raw materials, measured by weight: 70-90 parts of polylactic acid, 0.1-5 parts of infrared stimulus responsive material, 5-18 parts of hydroxyapatite, 0.1-5 parts of bone active drug, 0.1-0.5 parts of antioxidant, and 0.1-0.5 parts of lubricant; the infrared stimulus responsive material comprises one or more of two-dimensional transition metal carbide (MXene), carbon quantum dots or black phosphorus.

[0010] In the present invention, PLA is used as a substrate, and raw materials such as infrared stimulus response materials, hydroxyapatite, and bone active drugs are used to prepare 3D printable bone repair materials. Under the stimulation of external near-infrared light, the infrared stimulus response material will generate heat, which can accelerate the release of hydroxyapatite and bone active drugs in the PLA matrix, thereby accelerating bone repair. At the same time, hydroxyapatite can also improve the mechanical strength of the material itself and enhance printing formability.

[0011] Preferably, the mass fraction of hydroxyapatite is 5-15 parts, and the mass fraction of polylactic acid is 80-90 parts. The more hydroxyapatite, the more beneficial it is to the bone repair speed, but too much hydroxyapatite will lead to a decrease in printing performance.

[0012] The polylactic acid includes L-polylactic acid and / or D-polylactic acid, and has a melt index of 1-20 g / 10 min; preferably, the melt index is 1-10 g / 10 min.

[0013] The antioxidant includes one or more of Irganox 1076, 1010, and 1098;

[0014] The lubricant includes one or more of ethylene bis stearamide (EBS), calcium stearate, and zinc stearate.

[0015] The particle size of the hydroxyapatite is 150-400 mesh; when the particle size of the hydroxyapatite is too large, the dispersion may not be uniform.

[0016] Preferably, the infrared stimulus responsive material is MXene with a purity of ≥99%; preferably, the mass fraction of the infrared stimulus responsive material is 0.5-2 parts. When the content of MXene exceeds 2 parts, there is no obvious effect and it has a certain impact on the printing performance.

[0017] The bone active drug includes one or more of Chinese medicine monomers, growth factors or icariin. The properties of these drugs are relatively stable, and the efficacy of the drugs will not be affected during the preparation of wires and photothermal irradiation. Light and thermal stimulation promote the degradation of the wires and release the drugs synchronously.

[0018] The Chinese medicine monomers include one or more of tanshinone, total flavonoids of rhizoma drynariae, astragaloside IV, etc.;

[0019] The present invention also provides a method for preparing the 3D printed bone repair material, comprising the steps of: mixing polylactic acid, infrared stimulus responsive material, hydroxyapatite, bone active drugs, antioxidants, and lubricants according to the raw material composition, and preparing wires after melt extrusion.

[0020] The temperature of the melt extrusion is 160-180° C., the number of revolutions is 150-300 rpm, and the wire diameter of the wire is 1.75±0.05 mm.

[0021] The present invention also provides the use of the 3D printed bone repair material in preparing a bone repair implant scaffold.

[0022] After implantation, the bone repair implant scaffold is irradiated with infrared light to activate the release of bone active drugs. The infrared light waveband used is 700-900nm or 1000-1700nm, and the irradiation lasts for 3-8min.

[0023] The bone repair implant scaffold is prepared by 3D printing of bone repair materials, the printing temperature is 200-230° C., and the base plate temperature is 40-60° C. The preparation method is simple and has no complicated post-processing process, and has excellent mechanical properties.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The 3D-printed bone repair material of the present invention uses PLA as a substrate and is combined with raw materials such as a stimulus-responsive material, hydroxyapatite, and a bone-active drug to form a 3D-printed bone repair material that can efficiently promote bone repair and also has excellent mechanical properties and 3D printing formability. The printed scaffold model has good flexibility and high mechanical strength.

[0026] (2) The infrared stimulus responsive material of the present invention can accelerate the release of hydroxyapatite and bone active drugs in the PLA matrix under the action of infrared light, thereby greatly improving the bone repair speed and achieving a good and fast repair effect.

[0027] (3) The material of the present invention is biocompatible and can be directly degraded in the body without causing any other side effects to the body. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is an illustration of the 3D printed bone repair scaffold model in the application example.

[0029] Figure 2 The Live-Dead graph of cells in the bone scaffolds of Comparative Example 1 and Example 2 on the 3rd day. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.

[0031] The raw materials used in the following specific embodiments are all purchased from the market, among which PLA is Total LX175, the antioxidant is Irganox 1076, the lubricant is ethylene bis stearamide (EBS), hydroxyapatite, MXene, icariin, etc. are all purchased from the market, and the particle size of hydroxyapatite is 300 mesh.

[0032] Comparative Example 1

[0033] According to mass parts, 98.6 parts of PLA, 1 part of bone active drug, 0.2 parts of 1076 and 0.2 parts of EBS were mixed evenly and added to a twin-screw extruder for granulation. The first section was 165°C, the second section was 170°C, the third section was 175°C, the fourth section was 180°C, the fifth section was 180°C, the sixth section was 180°C, the seventh section was 180°C, the eighth section was 180°C, the ninth section was 180°C, and the tenth section was 175°C. The number of revolutions was 300rpm. After the sample was dried, it was drawn at a drawing temperature of 200°C to obtain a wire with a diameter of 1.75 mm.

[0034] Comparative Example 2

[0035] According to mass parts, 83.6 parts of PLA, 1 part of bone active drug, 15 parts of hydroxyapatite, 0.2 parts of 1076, and 0.2 parts of EBS were mixed evenly and added to a twin-screw extruder for granulation. The first section was 165°C, the second section was 170°C, the third section was 175°C, the fourth section was 180°C, the fifth section was 180°C, the sixth section was 180°C, the seventh section was 180°C, the eighth section was 180°C, the ninth section was 180°C, and the tenth section was 175°C. The number of revolutions was 300rpm. After the sample was dried, it was drawn at a drawing temperature of 200°C to obtain a wire with a diameter of 1.75 mm.

[0036] Example 1

[0037] According to mass parts, 82.6 parts of PLA, 15 parts of hydroxyapatite, 1 part of MXene, 1 part of bone active drug, 0.2 parts of 1076, and 0.2 parts of EBS were mixed evenly and added to a twin-screw extruder for granulation. The first section was 165°C, the second section was 170°C, the third section was 175°C, the fourth section was 180°C, the fifth section was 180°C, the sixth section was 180°C, the seventh section was 180°C, the eighth section was 180°C, the ninth section was 180°C, and the tenth section was 175°C. The number of revolutions was 300rpm. After the sample was dried, it was drawn at a drawing temperature of 200°C to obtain a wire with a diameter of 1.75 mm.

[0038] Example 2

[0039] According to mass parts, 81.6 parts of PLA, 15 parts of hydroxyapatite, 2 parts of MXene, 1 part of bone active drug, 0.2 parts of 1076, and 0.2 parts of EBS were mixed evenly and added to a twin-screw extruder for granulation. The first section was 165°C, the second section was 170°C, the third section was 175°C, the fourth section was 180°C, the fifth section was 180°C, the sixth section was 180°C, the seventh section was 180°C, the eighth section was 180°C, the ninth section was 180°C, and the tenth section was 175°C. The number of revolutions was 300rpm. After the sample was dried, it was drawn at a drawing temperature of 200°C to obtain a wire with a diameter of 1.75 mm.

[0040] Comparative Example 3

[0041] According to mass parts, 77.6 parts of PLA, 20 parts of hydroxyapatite, 1 part of MXene, 1 part of bone active drug, 0.2 parts of 1076, and 0.2 parts of EBS were mixed evenly and added to a twin-screw extruder for granulation. The first section was 165°C, the second section was 170°C, the third section was 175°C, the fourth section was 180°C, the fifth section was 180°C, the sixth section was 180°C, the seventh section was 180°C, the eighth section was 180°C, the ninth section was 180°C, and the tenth section was 175°C. The number of revolutions was 300rpm. After the sample was dried, it was drawn at a drawing temperature of 200°C to obtain a wire with a diameter of 1.75 mm.

[0042] The wires prepared in the examples and comparative examples were Figure 1 The model shown is printed into an implantable bone scaffold with a printing temperature of 210° C. and a base plate temperature of 50° C. to obtain an implantable bone scaffold.

[0043] GB / T 1040 was used to test the tensile properties of the wire, and the results are shown in Table 1. C1, C2, and C3 correspond to the mechanical properties and formability of the samples prepared in Examples 1, 2, and 3, respectively, and D1 and D2 correspond to the mechanical properties and formability of the samples prepared in Examples 1 and 2, respectively. From the data in Table 1, it can be seen that the addition of 15 parts of hydroxyapatite greatly improves the mechanical properties and printing performance, but after the content of hydroxyapatite is increased to 20 parts, the tensile strength in the Z-axis direction decreases and the printing formability deteriorates.

[0044] Table 1 Tensile properties and printing properties of wires in different embodiments

[0045] Serial number C1 C2 D1 D2 C3 XY direction tensile strength (MPa) 45 50 51 51 55 Tensile strength in Z-axis direction (MPa) 30 35 35 38 14 Formability middle good good good Difference

[0046] Application Example 1

[0047] The wire-printed stent of Comparative Example 1 was irradiated with 808 nm near-infrared light for 5 min, and the stent was recorded as A1. The wire-printed stent of Comparative Example 2 was irradiated with 808 nm near-infrared light for 5 min, and the stent was recorded as A2. The wire-printed stent of Comparative Example 3 was irradiated with 808 nm near-infrared light for 5 min, and the stent was recorded as A3.

[0048] The wire-printed stent of Example 1 was irradiated with 808nm near-infrared light for 2 minutes, and the stent was recorded as B1. The wire-printed stent of Example 1 was irradiated with 808nm near-infrared light for 5 minutes, and the stent was recorded as B2. The wire-printed stent of Example 2 was irradiated with 808nm near-infrared light for 5 minutes, and the stent was recorded as B3. The above stents were used to conduct bone active drug release rate and cell experiments.

[0049] 1. Release rate of bone active drugs

[0050] The scaffold prepared in Application Example 1 was immersed in simulated body fluid (SBF) for different time periods using an ultraviolet spectrophotometer to detect the concentration of icariin in the solution, thereby determining the release rate of icariin. The test results are shown in Table 2. From the data in Table 2, it can be seen that the release rate of icariin can be controlled by controlling the addition of infrared stimulus response materials and controlling the irradiation time.

[0051] Table 2 Icariin concentration in SBF of bone scaffolds prepared in Application Example 1 (umol / L)

[0052] Soaking time A1 A2 B1 B2 B3 A3 4 weeks 12.36 12.35 32.21 41.38 43.41 43.72 8 weeks 24.73 24.72 53.53 62.72 63.13 63.41

[0053] 2. Biocompatibility

[0054] Rat bone marrow mesenchymal stem cells (rBMSCs) purchased from the Cell Bank of the Chinese Academy of Sciences in Shanghai (Catalog No. SCSP-402) were cultured at 1×10 4 The density of cells was seeded on the support of a 24-well plate. After 24 hours and 72 hours of co-culture, the cell compatibility was detected using the thiazole blue colorimetric method (MTT method). 100μL of 5mg / mL MTT solution was added to each well, reacted in a cell culture incubator for 4 hours, and then 1mL DMSO was used to dissolve the crystals. Then 100ul of liquid was aspirated into a 96-well plate, and the absorbance value (OD value) was measured at a wavelength of 490 nanometers using an automatic microplate reader (Bio Tek, USA). Within a certain range of cell numbers, the absorbance value is proportional to the number of cells, and the results are shown in Table 3.

[0055] As can be seen from the table, adding only hydroxyapatite has little effect on the number of living cells. After adding MXene, the number of living cells also increases significantly without the stimulation of near-infrared light in the external environment, and the OD value increases from 0.555 to 0.65. After adding infrared light stimulation externally, the OD value can be increased to 0.775. As the detection time is extended from 24h to 72h, the OD value will increase.

[0056] Table 3 OD values ​​of bone scaffold models prepared by wire rods in different embodiments

[0057] time A1 A2 B1 B2 B3 A3 24h 0.555 0.574 0.65 0.775 0.786 0.781 72h 0.788 0.812 0.87 1 1.102 1.01

[0058] 3. Cell proliferation test

[0059] rBMSCs were plated at 1×10 per well. 4 The cells were seeded at a density of 100 cells on the bone scaffolds B2 and A1 in a 24-well plate, and live / dead double staining was performed after 3 days of co-culture. The Live-Dead graph shows the cell growth of the bone scaffolds on the third day after infrared irradiation. Green is live cells, red is dead cells, and the cells grow on the scaffolds and along the outline of the scaffolds.

[0060] The results are as follows Figure 2 As shown, Figure 2 (a) is the Live-Dead image of the stent printed by the A1 wire prepared in Comparative Example 1 on the 3rd day, Figure 2 (b) is the Live-Dead image of the scaffold printed by the B2 wire prepared in Example 1 on the 3rd day. It can be seen that the number of living cells of B2 is significantly greater than that of A1, indicating that infrared stimulation can make the MXene material heat up, which can promote the release of hydroxyapatite and active drugs and significantly accelerate the speed of bone repair.

[0061] Application Example 2

[0062] Thirty Sprague-Dawley rats (male, 300-350 g, 8 weeks old) were used to establish a femoral condyle defect model: a 3 cm skin incision was made on the lateral side of the left femur, and the periosteum was peeled off from the lateral surface of the distal femoral epiphysis. bone defects. Normal saline was injected for flushing to remove bone fragments and heat generated during drilling. All SD rats were randomly divided into 6 groups and implanted with different scaffolds and received different intervention treatments. The defect site was irradiated with 808nm near-infrared laser for 5 minutes every other day to maintain the local temperature at 42.0±0.5℃. At 4 and 8 weeks after surgery, the rats were killed, and the femurs were removed and fixed in 4% paraformaldehyde solution to evaluate bone regeneration.

[0063] The wire-printed stent of Comparative Example 1 was implanted into rats and irradiated with 808 nm near-infrared light for 5 min. This group of rats was designated as E1.

[0064] The wire-printed stent of Comparative Example 2 was implanted into rats and irradiated with 808 nm near-infrared light for 5 min. This group of rats was designated as E2.

[0065] The stent printed by the wire material of Example 1 was implanted into rats and irradiated with 808 nm near-infrared light for 2 min. This group of rats was designated as F1.

[0066] The stent printed by the wire material of Example 1 was implanted into rats and irradiated with 808 nm near-infrared light for 5 min. This group of rats was designated as F2.

[0067] The wire-printed stent of Example 2 was implanted into rats and irradiated with 808 nm near-infrared light for 5 min. This group of rats was designated as F3.

[0068] The wire-printed stent of Comparative Example 3 was implanted into rats and irradiated with 808 nm near-infrared light for 5 min. This group of rats was designated as E3.

[0069] After the rats were killed at 4 weeks and 8 weeks, the femur samples were taken out and fixed in 4% paraformaldehyde solution. The bone volume (BV), trabecular thickness (Tb.Th), and trabecular gap (Tb.Sp) data were quantified by high-resolution micro-computed tomography (micro-CT; Siemens, Germany). The results are shown in Table 4. It can be seen from the data in the table that the addition of MXene and the stimulation of external infrared light can significantly increase the bone volume and trabecular thickness, and reduce the trabecular gap. MXene can generate heat under the stimulation of external infrared light, which can accelerate the release of hydroxyapatite and bone active drugs.

[0070] Table 4 Bone volume, trabecular thickness and trabecular spacing of different rats at 4 and 8 weeks

[0071]

Claims

1. A 3D printed bone repair material, characterized in that: The raw material composition includes, by weight: 70-90 parts of polylactic acid, 0.1-5 parts of infrared stimulus response material, 5-18 parts of hydroxyapatite, 0.1-5 parts of bone active drug, 0.1-0.5 parts of antioxidant, and 0.1-0.5 parts of lubricant; The infrared stimulus responsive material includes one or more of MXene, carbon quantum dots or black phosphorus.

2. The 3D printed bone repair material according to claim 1, characterized in that: The mass fraction of the hydroxyapatite is 5-15 parts, and the mass fraction of the polylactic acid is 80-90 parts.

3. The 3D printed bone repair material according to claim 1, characterized in that: The polylactic acid includes L-polylactic acid and / or D-polylactic acid, and has a melt index of 1-20 g / 10 min; The antioxidant includes one or more of Irganox 1076, 1010, and 1098; The lubricant includes one or more of ethylene bis stearamide, calcium stearate, and zinc stearate.

4. The 3D printed bone repair material according to claim 1, characterized in that: The particle size of the hydroxyapatite is 150-400 meshes; the bone active drug includes one or more of traditional Chinese medicine monomers, growth factors or icariin.

5. The method for preparing a 3D printed bone repair material according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: mixing polylactic acid, infrared stimulus response material, hydroxyapatite, bone active medicine, antioxidant and lubricant according to the raw material composition, and preparing wire material after melt extrusion.

6. The method for preparing a 3D printed bone repair material according to claim 5, characterized in that: The temperature of the melt extrusion is 160-180° C., the number of revolutions is 150-300 rpm, and the wire diameter of the wire is 1.75±0.05 mm.

7. Use of the 3D printed bone repair material according to any one of claims 1 to 4 in the preparation of a bone repair implant scaffold.

8. The use of the 3D printed bone repair material according to claim 7 in preparing a bone repair implant scaffold, characterized in that: The bone repair implant bracket is irradiated with infrared light after implantation to accelerate the release of hydroxyapatite and bone active drugs.

9. The use of the 3D printed bone repair material according to claim 7 in preparing a bone repair implant scaffold, characterized in that: The infrared light band used is 700-900nm or 1000-1700nm, and the irradiation time is 3-8min.

10. The use of the 3D printed bone repair material according to claim 7 in preparing a bone repair implant scaffold, characterized in that: The bone repair implant scaffold is made by 3D printing bone repair material, the printing temperature is 200-230°C, and the base plate temperature is 40-60°C.

Citation Information

Patent Citations

  • MXene composite bone repair material having photothermal function and preparation method thereof

    CN110935059A

  • 3D printing bone tissue repair scaffold material and preparation method thereof

    CN115737931A

Cited By

  • Preparation method of porous composite material based on hydroxyapatite, magnesium oxide and tannic acid

    CN121371323A